PENGARUH MOTIVASI BELAJAR, PENYALAHGUNAAN TEKNOLOGI INFORMASI DAN INTEGRITAS MAHASISWA TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI SEBAGAI CALON AKUNTAN (Studi Kasus Pada Mahasiswa Akuntansi Universitas Islam Malang) - Chandra Febyani Putri Mulyadi; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
The purpose of this study is to determine the effect of learning motivation, misuse of information technology and student integrity on the academic cheating behavior of accounting students as prospective accountants for accounting students at the Islamic University of Malang. This research is an associative quantitative research and uses a descriptive quantitative design. Data collection was collected using a questionnaire. The sample used by the researchers using purposive sampling technique, and using the slovin formula calculation determine the number. The technique used by the researcher is Multiple Linear Regression Analysis with the help of SPSS 21.The results of this study stated that learning motivation and student integrity have no effect on the academic cheating behavior of accounting students as prospective accountants, while the misuse of information technology has a significant positive effect on the academic cheating behavior of accounting students as prospective accountants. And simultaneously all independent variables affect the dependent variable.Keywords : learning motivation, misuse of information technology, student integrity, academic cheating behavior.